2017
DOI: 10.1016/j.aogh.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Transculturalizing Diabetes Prevention in Latin America

Abstract: Successful transculturalization strategies have been implemented in screening tools and prevention programs in LA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 47 publications
1
24
1
8
Order By: Relevance
“…On the other hand, a random sample of 521 participants recruited from the EVESCAM study showed that a LA-FINDRISC >10 had a sensitivity of 63% and a specificity of 61% for predicting glucose metabolism impairment, with an AUC of 0.68 [7]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, a random sample of 521 participants recruited from the EVESCAM study showed that a LA-FINDRISC >10 had a sensitivity of 63% and a specificity of 61% for predicting glucose metabolism impairment, with an AUC of 0.68 [7]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LA-FINDRISC was also evaluated in two primary care centers in Uruguay, where a total of 109 subjects were included and it was shown that a score >14 had a sensitivity of 70% and a specificity of 66% for predicting unknown diabetes or prediabetes [7]. Although the cutoff point found in this study is similar to ours, the differences in sensitivity may be due to the fact that the subjects evaluated in Uruguay had been enrolled from clinical centers and therefore are not necessarily representative of the general population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations